Geodynamics, rifting, stratiform and stratabound mineral deposits - Dingemans, D.R.W. (Rhodes University, Faculty of Science, Department of Geology, 1981)
Stratiform and stratabound ore deposits commonly show a direct relationship with rifts. This association is studied by developing a geodynamic model of mantle processes and crustal responses. The geodynamics of the earth can be modelled by the process of mantle advection, which involves the episodic generation and segregation of low density mantle diapirs and their rise and subsequent interaction with the crust. The theory of mantle advection explains the genetic association between rifting, magmatism, basin development and subsequent orogeny and metamorphism. Global evolution has passed through a number of major stages of non-uniformitarian development in which each cycle was characterized by fairly uniform behaviour terminated by intense geodynamic upheaval. The relationship between geological evolution and mantle advection is examined by reviewing the major characteristics of each of the cycles, which correspond to the Archean, Early Proterozoic, Mid Proterozoic, Late Proterozoic-Palaeo2oic, and Mesozoic - Cainozoic eras. Although mentle advection has controlled crustal processes throughout time, the decrease in the thermal energy of the earth has caused >the major evolutionary changes in response to thickening and a greater rigidity of the sialic crust. Rifts are penetrative taphrogenic faults in the earths crust which act as major conduits for the transfer of magmas, from the mantle and lower crustal levels, to the upper crust and the surface. Rifts are also permeable zones for the migration of metalliferous brines, generated by magmatic differentiation. These metalliferous brines would either be exhaled at surface to form stratiform volcanogenic and volcanosedimentary ore deposits , or would interact with preferential host horizons to form stratabound ore deposits . The associat ion between rifting and stratiform and stratabound ore deposits is illustrated by examining :he tectonic setting, and st ratigraphic relationships of typical ore deposit types .
Keywords: Ore deposits; Geodynamics; Mines and mineral resources; Rifts (Geology)